The Habitat Use and Feeding Activity of Tadarida plicata in Thailand - Utthammachai, Kessarin; Bumrungsri, Sara; Chimchome, Vijak; Russ, Jon; Mackie, Iain (วารสารวนศาสตร์ไทย, 2022)
The study quantified feeding rate and habitat use of Tadarida plicata demonstrated the important role they play in the natural and cultivated ecosystems. This study determined habitat use and feeding activity of T. plicata in an agricultural landscape including seasonal variation in habitat use and foraging activity. The proportion of signal-receiving time over the total recording time was measured to obtain an estimate of the relative activity of bats within each habitat. It was found that bats selected villages and dry rice fields. This is probably because these habitats supported higher insect densities. In addition, it was used the number of feeding buzzes per unit of activity time to calculate an index of attack rate by bats. Bat activities at each site were estimated by calculating the average number of bats passes per minute. Analysis of Variance was conducted to examine differences in mean attack attempt (numbers of feeding buzzes per unit of activity time) between recording sessions, among habitats and seasons. Keywords: Tadarida plicata, Habitat use, Feeding activity, Seasonal variation